Potentiality at play : an exploration of constructivist art museum pedagogy - Ho, Wena Wing Wa (2022)
In the wake of a paradigm shift in contemporary museum education in the 21st century, the conventional ways of learning have been transcended. Constructivism as a lens to rethink learning in art museums underlines active participation of learners and facilitation by the educators during the meaning-making process. Such pedagogical approach acknowledges the potentiality of becoming, of the educators, learners and learning itself. Existing literature has shown that art museum education is an understudied and undertheorized profession that lacks a coherent philosophy shared by practitioners. As one of the first studies that focuses on the context of constructivist art museum education, this study aims to explore the characteristics and practices of constructivist art museum pedagogy. A qualitative ethnographic approach used in this single case study that involves field observation and interviews at Jyväskylä Art Museum in Finland yields the results in three main aspects: an open heart that emancipates learners, playfulness knits a flexible fabric for educators and facilitative-and-participatory learning in motion, while also highlights learning space as a result and catalyst of museum pedagogy. This study contributes to the conceptualization of a philosophy to be shared by museum educators and adds nuances to the understanding of museum pedagogical practices.